Analysis of the pyrolytic fuel properties of empty fruit bunch briquettes - Nyakuma, Bemgba Bevan (2012)
Briquetting is technique for mechanically compacting and densifying loose materials into a uniform solid fuel aimed at improving the physical and thermochemical properties such as energy density, moisture content. This study is aimed at investigating the pyrolytic fuel properties of briquettes using DSC thermal analysis. The EFB Briquettes were pulverized and sieved in a Retsch analysis sieve with screen size 800 micron. The Higher Heating Value (HHV) of the fuel was determined using a bomb calorimeter according to the ASTM standard D-2015 technique. Proximate analysis was carried to determine the moisture content, volatile matter, fixed carbon and ash content of the fuel. The powdered EFB briquette was analyzed using a Perkin Elmer DSC 7 thermal analyzer under pyrolysis conditions from 30 to 500°C at a constant heating rate of 10°C min-1 with nitrogen (N2), flow rate of 25 mL min-1 as sweeping gas. The calorific changes during DSC analysis were recorded and analyzed. A Scanning Electron Microscope (SEM) was used to investigate the surface composition and particle size distribution of the fuel. Surface analysis revealed that 57% of the fuel particles are in the 151-250 μm range. The HHV value of the fuel obtained was 17.57 MJ kg-1 and specific heat Cp = 1,397 J kg-1 K-1. From the FTIR spectra of the fuel, the product gases as H2, CO, CO2, CH4 and CmHn can be reasonably predicted. The results indicated that EFB briquette has good fuel properties and can be utilized as a fuel in biomass pyrolysis.